Rectal Thiopental versus Intramuscular Ketamine in Pediatric Procedural Sedation and Analgesia; a Randomized Clinical Trial - Azizkhani, Reza; Esmailian, Mehrdad; shojaei, Azadeh; Golshani, Keihan (Archives of Academic Emergency Medicine, 2018)
Introduction:Â Physicians frequently deal with procedures which require sedation of pediatric patients. Laceration repair is one of them. No study has been performed regarding the comparison between induction of sedation with sodium thiopental and ketamine in laceration repair. Therefore, the present study was aimed to comparison of induced sedation by rectal sodium thiopental and muscular injection of hydrochloride ketamine in pediatric patients need laceration repair.Â Methods:Â The presented study is a single-blinded clinical trial performed through 2013 to 2014 in Ayatollah Kashani and Alzahra Hospitals, Isfahan, Iran. Patients from 3 months to 14 years, needed sedation for laceration repair, were entered. Patients were sequentially evaluated and randomly categorized in two groups of hydrochloride ketamine with dose of 2-4 milligram per kilogram and sodium thiopental with dose of 25 milligram per kilogram. Demographic data and vital signs before drug administration and after induction of sedation, Ramsey score, time to onset of action, and sedation recovery time were evaluated. Chi-squared, Mann-Whitney, and Non-parametric analysis of covariance tests were used. P<0.05 was considered as a significant level.Â Results:Â In this study 60 pediatric patients were entered. 30 patients with mean age of 42.8Â±18.82 months were received sodium thiopental and the rest with mean age of 30.08Â±16.88 months given ketamine. Mann-Whitney test was showed that time to onset of action in sodium thiopental group (28.23Â±5.18 minutes) was significantly higher than ketamine (7.77Â±4.13 minutes), (p<0.001). The sedation recovery time in ketamine group (29.83Â±7.70) was higher than sodium thiopental. Depth of sedation had no significant difference between two groups based on Ramsey score (p=0.87). No significant difference was seen between two groups in the respiratory rate (df=1, 58; F=0.002; P=0.96) and heart rate (df=1, 58; F=0.98; P=0.33). However, arterial oxygen saturation level (df=1, 58; F=6.58; P=0.013) was significantly higher in ketamine group.Â Conclusion:Â The findings of the present study show that Although the recovery time from sedation by ketamine is more than sodium thiopental, itâ€™s fast-acting function without effecting on the oxygen saturation level causes that ketamine is considered as the better choice for induction of sedation in pediatric patients need laceration repair. In addition, long-term effect of ketamine provides more time for the physician to do the procedure and this issue decreases the need probability to the repeated-dose. However, effectiveness of both drugs to decrease the agitation was equal, based on the Ramsey score.